Pseudomonas-Specific NGS Assay Provides Insight Into Abundance and Dynamics of Pseudomonas Species Including P. aeruginosa in a Cooling Tower - Pereira, Rui P. A.; Peplies, Jörg; Mushi, Douglas; Brettar, Ingrid; Höfle, Manfred G. (Frontiers in Microbiology, 2018)
Pseudomonas species are frequent inhabitants of freshwater environments and colonizers of water supply networks via bioadhesion and biofilm formation. P. aeruginosa is the species most commonly associated with human disease, causing a wide variety of infections with links to its presence in freshwater systems. Though several other Pseudomonas species are of ecological and public health importance, little knowledge exists regarding environmental abundances of these species. In the present study, an Illumina-based next-generation sequencing (NGS) approach using Pseudomonas-specific primers targeting the 16S rRNA gene was evaluated and applied to a set of freshwater samples from different environments including a cooling tower sampled monthly during 2 years. Our approach showed high in situ specificity and accuracy. NGS read counts revealed a precise quantification of P. aeruginosa and a good correlation with the absolute number of Pseudomonas genome copies in a validated genus-specific qPCR assay, demonstrating the ability of the NGS approach to determine both relative and absolute abundances of Pseudomonas species and P. aeruginosa. The characterization of Pseudomonas communities in cooling tower water allowed us to identify 43 phylotypes, with P. aeruginosa being the most abundant. A shift existed within each year from a community dominated by phylotypes belonging to P. fluorescens and P. oleovorans phylogenetic groups to a community where P. aeruginosa was highly abundant. Co-occurrence was observed between P. aeruginosa and other phylotypes of P. aeruginosa group as well as the potentially pathogenic species P. stutzeri, but not with phylotypes of the P. fluorescens group, indicating the need to further investigate the metabolic networks and ecological traits of Pseudomonas species. This study demonstrates the potential of deep sequencing as a valuable tool in environmental diagnostics and surveillance of health-related pathogens in freshwater environments.